(untitled) (Revista Direito em Debate, 2024)
This research intends to investigate the equal conditions for access and permanence in higher education, from the perspective of the fundamental right to democracy itself. Regarding the methods of literature review, deductive and qualitative, the main objective of the work is to analyze the fundamental direction of equality of conditions for access and permanence not in higher education can contribute and, in the positive case, in what way, to strengthen humanistic training of students, which represents two pillars of the success of public and private universities, and ensures the fundamental right of democracy, which is more than a periodic “electoral obrigação”, because its societal rules are not contemplated only on each two /four years. But rather than the dialogue itself – which is also the effort that Paulo Freire denotes to the sense of revolution (radical transformation in practice) – once it is not possible to dialogue with antagonists, for example, those who are validated by the absolute exclusion, ou seja, it is not possible to tolerate (democratically) negative intolerance. In the end, it was concluded that the right, the fundamental right to equal conditions for access and permanence in higher education, has a broad constitutional and legal foundation, with the potential to strengthen defensive democracy, linked to the struggle to defend the most basic rights, as well as how to increase a true propositional democracy, promoting resilience in the face of possible present and future setbacks, being essential to the exercise of democracy itself, as a human and fundamental right.